Semi-Automatic Methodology for Fire Break Maintenance Operations Detection with Sentinel-2 Imagery and Artificial Neural Network - Pereira-Pires, João (2021)
PTDC/CCI-COM/30344/2017 PCIF/SSI/0102/2017 UID/EEA/00066/2019 UIDB/00239/2020